2017
DOI: 10.1038/am.2017.141
|View full text |Cite
|
Sign up to set email alerts
|

Easy on-demand self-assembly of lateral nanodimensional hybrid graphene oxide flakes for near-infrared-induced chemothermal therapy

Abstract: Near-infrared (NIR)-induced chemothermal doxorubicin (DOX) release for anticancer activity was demonstrated using DOX-incorporated fully lateral nanodimensional graphene oxide (nGO) flakes layered with chitosan-polyethylene glycol (PEG) conjugate (nGO@DOX-cPEG) from a single-pass gas-phase self-assembly. Unlike most previously reported graphene oxide-based drug carriers, the proposed processing method introduced a fully nanoscale (both in lateral dimension and thickness) configuration without multistep wet phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Upon exposure to near-infrared (NIR) irradiation, the photosensitizer converts the absorbed light energy into thermal energy and generates singlet oxygen ( 1 O 2 ) from tissue oxygen, ultimately resulting in local hyperthermia and tumor damage (necrosis and/or apoptosis) 2 . NIR-triggered tumor ablation has particular advantages over conventional therapeutic methods, including high and precise local temperature, preservation of surrounding tissues, short recovery time, destruction of tumor vessels, induction of acute inflammatory responses, and deprivation of oxygen and nutrients in tumor areas 3 , 4 . However, their limited accumulation in tumor, water-insoluble characteristics, and instability restrict the application of photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to near-infrared (NIR) irradiation, the photosensitizer converts the absorbed light energy into thermal energy and generates singlet oxygen ( 1 O 2 ) from tissue oxygen, ultimately resulting in local hyperthermia and tumor damage (necrosis and/or apoptosis) 2 . NIR-triggered tumor ablation has particular advantages over conventional therapeutic methods, including high and precise local temperature, preservation of surrounding tissues, short recovery time, destruction of tumor vessels, induction of acute inflammatory responses, and deprivation of oxygen and nutrients in tumor areas 3 , 4 . However, their limited accumulation in tumor, water-insoluble characteristics, and instability restrict the application of photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to adequately deliver GO nanoflakes into the tumor area, the nanoflakes were coated with both PEG and chitosan in the liquid phase and were then administered to treat various cancer types. A biodistribution study demonstrated that the delivery and delivery speed of chitosan-coated nanoparticles into the tumor area were significantly increased compared with the non-coated nanoparticles, therefore leading to an enhanced targeted antitumor effect (Thapa et al 2017 ). The use of biodegradable and disintegrable inorganic nanosystems for cancer treatment has become dramatically more frequent due to the nanopaticles’ less toxic effects on vital organs.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…此 外, 有机小分子化合物还可以通过非共价键作用对 GO 进行表面修饰, 如静电力、范德华力、氢键和π-π堆积作 用等 [15] . 通过π-π堆积作用, 可以将具有芳香环结构的 抗癌药物修饰到 GO 表面(图 3), 如阿霉素(DOX) [64,65] 和 喜树碱(CPT) [66,67] , 进而将药物递送到肿瘤细胞与组 织 [68] . 例如, 利用 π-π 堆积和疏水作用将 DOX 装载到转 铁蛋白(Tf)与 PEG 修饰的 GO (Tf-PEG-GO)表面, 装载 效率可达 115.4%, 对大鼠 C6 神经胶质瘤具有良好的靶 向治疗效果 [69] .…”
Section: N-(3-二甲氨丙基)-n'-乙基碳二亚胺(edc)/n-羟基丁二unclassified